2014
DOI: 10.4172/2324-9110.s1-002
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Voltage Potentials and the Microenvironment: Bioelectric Signals that Reveal, Induce and Normalize Cancer

Abstract: Cancer may be a disease of geometry: a misregulation of the field of information that orchestrates individual cells’ activities towards normal anatomy. Recent work identified molecular mechanisms underlying a novel system of developmental control: bioelectric gradients. Endogenous spatio-temporal differences in resting potential of non-neural cells provide instructive cues for cell regulation and complex patterning during embryogenesis and regeneration. It is now appreciated that these cues are an important la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
143
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(147 citation statements)
references
References 438 publications
(388 reference statements)
3
143
0
1
Order By: Relevance
“…; Zuberi et al. ; Chernet & Levin ; Yang & Brackenbury ). One important aspect of endogenous bioelectricity is resting potential or V mem (Levin ).…”
Section: Introductionmentioning
confidence: 99%
“…; Zuberi et al. ; Chernet & Levin ; Yang & Brackenbury ). One important aspect of endogenous bioelectricity is resting potential or V mem (Levin ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study concluded that depolarization of a glycine receptorexpressing channel in Xenopus Laevis neural crest may induce a full metastatic melanoma without any involvement of a mutation, carcinogen, or DNA damage (Blackiston et al 2011). Deregulation of the bioelectric environment may rewire protein interaction networks (Taylor et al 2009), and comprehensive reviews of the role of bioelectric processes in cancer, highlighting how bioelectric activity is a constitutive partner of the morphogenetic field involved during cancer transformation, have also been published (Chernet and Levin 2013).…”
Section: Toft and Organicismmentioning
confidence: 99%
“…Ion channel selectivity and electric field-sensing are crucial to bioelectrical activity. [18][19][20] The bioelectrical characteristics of commercially available protein ion channels and toxin poreformers can be used in bio-electronic interfaces and ionic a Dept. [18][19][20] The bioelectrical characteristics of commercially available protein ion channels and toxin poreformers can be used in bio-electronic interfaces and ionic a Dept.…”
Section: Introductionmentioning
confidence: 99%